Character education - Aydogan, I. (Культура народов Причерноморья, 2003)
In this study, the subject of character and character education, which has taken on a great significance in Europe and
the USA during the last years and become the biggest problem of modem people, is considered. As a result of
growth of negative development tendencies in the world that affect an individual, the subjects of the necessity of
character education and the duties of family and society are among the themes, being investigated. Besides, the role
of schools in the development of individuals' characters, where and how character education is to be held, the duties
of teachers and school administrators are considered in this work. In the article there are particular suggestions of
the way, how character education should be performed.